The development and management of visitor attractions - Swarbrooke, John, 1956- (London : Routledge, 2015)
Now in its second edition, The Development en Management of Visitor Attractions has been fully revised and updated to cover the latest issues in this ever-changing area of tourism. Among the new feature sand topics included in this edition are: A full range of over twenty international case studies drawn from twelve countries including: theme parks in the USA, Legoland in Denmark, nightclubs in Ibiza, and the attractions of Brazil and South Africa; Updated statistics and examples; Analysis of the Millennium Dome and other National Lottery funded projects. As behore, the author systematically outlines the factors that contribute to the success of visitor attractions. The text covers ever aspect of the process of developing and managing different kinds of attractions, and the theory is illustrated by a range of examples and case studies drawn from a number of countries.